Natural durability of five amazonian species in two different decay environments - Júlio Henrique Germano de Souza; Rafael Quirino dos Santos; Patrícia Aparecida Rigatto Castelo; Janaína De Nadai Corassa (Ciência Rural)
ABSTRACT: Understanding the natural durability of Amazonian wood species in different deterioration environments is essential to promote their sustainable use and extend their useful life in various applications. The present study evaluated the natural durability of five Amazonian wood species in open field and forest in Sinop, Mato Grosso, Brazil. The species evaluated were Parkia pendula (Willd.) Benth. ex Walp (Angelim Saia), Rauvolfia paraensis Ducke (Peroba d’Água), Goupia glabra Aubl. (Cupiúba), Aspidosperma populifolium A. DC. (Peroba-Mica) and Mezilaurus itauba (Meisn.) Taub. ex Mez (Itaúba). Two hundred samples were used, 40 of each species. Of these, 10 samples of each species were used to determine the apparent density at 12% humidity and then subjected to mechanical testing to obtain the modulus of elasticity and rupture through compression parallel to the fibers, so that these results could be used for comparison at the end of the weathering process. Another 30 samples of each species were exposed for 415 days in both environments mentioned and evaluated by the breakage test after exposure. Termites were collected for identification. After exposure, the health and resistance to compression parallel to the fibers were evaluated. Parkia pendula (0.56 ± 0.02 g/cm³) and Rauvolfia paraensis (0.70 ± 0.05 g/cm³) had the lowest densities, while Aspidosperma populifolium (0.72 ± 0.02 g/cm³), Goupia glabra (0.79 ± 0.03 g/cm³) and Mezilaurus itauba (0.80 ± 0.06 g/cm³) had the highest. Parkia pendula and Rauvolfia paraensis were the least durable in all tests, presenting a health index of 60.10%. In contrast, Mezilaurus itauba and Aspidosperma populifolium demonstrated the greatest durability, reaching 100%. The environment affected only two species: Goupia glabra was more affected in open field, and Rauvolfia paraensis in the forest. Only termites of the genus Nasutitermes were found, preferring Parkia pendula and Rauvolfia paraensis. The natural durability of Aspidosperma populifolium is statistically equivalent to that of Mezilaurus itauba. Aspidosperma populifolium and Mezilaurus itauba showed the greatest biological resistance to wood-boring termites in both environments analyzed, making them more suitable for areas prone to these insects, while Parkia pendula and Rauvolfia paraensis showed greater susceptibility to attack by Nasutitermes termites, regardless of the environment.